2019
DOI: 10.1016/j.immuni.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

MHC Class II Antigen Presentation by the Intestinal Epithelium Initiates Graft-versus-Host Disease and Is Influenced by the Microbiota

Abstract: Graft-versus-host disease (GVHD) in the gastrointestinal (GI) tract is the principal determinant of lethality following allogeneic bone marrow transplantation (BMT). Here, we examined the mechanisms that initiate GVHD, including the relevant antigen-presenting cells. MHC class II was expressed on intestinal epithelial cells (IECs) within the ileum at steady state but was absent from the IECs of germ-free mice. IEC-specific deletion of MHC class II prevented the initiation of lethal GVHD in the GI tract. MHC cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(215 citation statements)
references
References 64 publications
(74 reference statements)
13
192
0
Order By: Relevance
“…The modulation of MHCII expression by IECs has been linked to the capacity of microbes to attach to the epithelium, and to IFNg production in both human and murine models (Ivanov et al, 2009;Panja et al, 1998;Umesaki et al, 1995). MHCII expression by IECs has been recently associated with a variety of physiological, such as regulation of the stem cell niche, and pathological functions, such as CD4 + T cell-mediated inflammation during graft-versus-host disease, in part through interacting with gut resident T cells that provide cytokines (Biton et al, 2018;Koyama et al, 2019;Ladinsky et al, 2019). Our data suggests a model in which antigen presentation by IECs is instrumental for the differentiation of CD4-IELs, which may further enhance MHCII expression by IECs via IFNg production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation of MHCII expression by IECs has been linked to the capacity of microbes to attach to the epithelium, and to IFNg production in both human and murine models (Ivanov et al, 2009;Panja et al, 1998;Umesaki et al, 1995). MHCII expression by IECs has been recently associated with a variety of physiological, such as regulation of the stem cell niche, and pathological functions, such as CD4 + T cell-mediated inflammation during graft-versus-host disease, in part through interacting with gut resident T cells that provide cytokines (Biton et al, 2018;Koyama et al, 2019;Ladinsky et al, 2019). Our data suggests a model in which antigen presentation by IECs is instrumental for the differentiation of CD4-IELs, which may further enhance MHCII expression by IECs via IFNg production.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a role for intestinal epithelial cell (IEC)-mediated antigen presentation via MHCII in the regulation of intestinal CD4 + T cell function (Biton et al, 2018;Koyama et al, 2019). We therefore asked whether local MHCII expression by IECs is required for CD4-IEL differentiation or maintenance.…”
Section: Mhcii Expression On Epithelial Cells Modulates Cd4-iel Diffementioning
confidence: 99%
“…The exposure of IECs to microbes and consequently IFNγ secretion was essential for HLA-II expression. Interestingly, IFN-γ secretion during the course of GvHD within the murine gut was not only detected by CD4 + T cells but also type 1 innate lymphoid cells (ILC1s) (Koyama et al, 2019). HLA-II expression has also been described by human gut enteroid organoids after IFN-γ exposure (Koyama et al, 2019;Wosen et al, 2019), indicating that a similar mechanism might apply for the development of GvHD within humans.…”
Section: Hla-ii Molecules In Malignancies and Auto-inflammatory Diseasesmentioning
confidence: 99%
“…The gut is one of the first sites where a GvHD response evolves, and serves as a diagnostic marker for the prognosis of GvHD. Recent studies described the expression of MHC-II molecules on the surface of intestinal epithelial cells (IECs) within the ileum of mice upon IFN-γ exposure (Koyama et al, 2019). The gut microbiota contributed to the induction of HLA-II expression, and HLA-II molecules were absent in the ileum of germ-free mice.…”
Section: Hla-ii Molecules In Malignancies and Auto-inflammatory Diseasesmentioning
confidence: 99%
“…Thus, a primary goal for alloSCT is the prevention of acute gut GVHD while preserving GVL. We previously showed in pre-clinical models that donor CD4 + T cells are initially activated by recipient non-hematopoietic antigen-presenting cells (APC) within the gut, including epithelial cells that upregulate MHCII molecules (2, 3). Following this, donor-derived colonic dendritic cells (DC) also prime donor CD4 + T cells in mesenteric lymph nodes (mLN) and trigger T helper-cell differentiation, which serves to amplify and exacerbate GVHD (4).…”
Section: Introductionmentioning
confidence: 99%